2015
DOI: 10.1161/circulationaha.115.015221
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article “Impact of Annual Operator and Institutional Volume on Percutaneous Coronary Intervention Outcomes: A 5-Year United States Experience (2005–2009)”

Abstract: We appreciate Khera and colleagues for their interest in our study on the percutaneous coronary intervention (PCI) volume-outcome relationship.1 Khera and colleagues point out the limitations of using administrative claims data, some of which we have acknowledged in our article. Despite the inconsistencies and deficiencies in operator identification in the Nationwide Inpatient Sample (NIS) data set, our methodology has been well validated in previous studies. 2,3Among 457 498 PCIs identified in our data set, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 4 publications
(3 reference statements)
4
37
1
Order By: Relevance
“…Similar results were shown in previously published studies . These findings were consistent with the general observation that increased institutional experience is associated with better outcomes for various procedures …”
Section: Discussionsupporting
confidence: 93%
“…Similar results were shown in previously published studies . These findings were consistent with the general observation that increased institutional experience is associated with better outcomes for various procedures …”
Section: Discussionsupporting
confidence: 93%
“…Given the rather stable practice during the study period along with trainees of consistent levels of experience participating in the majority of procedures, we believe our institution to be well suited in the evaluation of our hypothesis. Annual complication rates at our facility are similar to nationally reported averages at similar high volume centers (4,18). Hence, our results can be assumed to be generalizable to similar high volume centers.…”
Section: Discussionsupporting
confidence: 82%
“…Badheka et al, using data from the Nationwide Inpatient Sample from 2005–2009, demonstrated higher risk-adjusted mortality among patients undergoing PCI performed by low- (< 16 PCIs/year) compared with high-volume operators (> 100 PCIs/year), though overall mortality was low. (10) However, this study was limited by its use of administrative rather than clinical data, and the method used to identify operators may have been less reliable than using NPI number. (23) In addition, data from both studies pre-date the publication of the Appropriate Use Criteria and the Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation (COURAGE) trial, which may have changed operator volumes (16,24).…”
Section: Discussionmentioning
confidence: 99%
“…(4,5) Contemporary, nationwide patterns of operator volumes have not been described, and little is known about the characteristics of procedures performed by low-volume operators. Furthermore, while prior studies have examined the volume-outcome relationship (610), none have been nationally representative using clinical data, or conducted after the change in the recommendations. Importantly, the operator volume recommendations were based on expert opinion that the increasing safety of PCI minimizes differences in outcomes across operators regardless of the number of procedures they perform, rather than on objective data.…”
Section: Introductionmentioning
confidence: 99%